In memoriam: Ernie Haerinck, 1949–2016 - Overlaet, Bruno (Proceedings of the Seminar for Arabian Studies, 2017)
Ernie Haerinck, who has died at the age of 67, was an exceptional scholar who made significant contributions to our understanding of the history and archaeology of Iran, Mesopotamia, and Arabia. His fieldwork took him to Iran, Bahrain, and the UAE. He was one of the pioneering archaeologists on both sides of the Gulf, in Iran, Bahrain, and particularly in the UAE where he will always be remembered for his work at the coastal site of ed-Dur (al-Dūr)